Marketing automation in Pega platform for telecommunications company - Samuseva, Katsiaryna (2020)
Master thesis is focused on business process automation, more precisely on marketing campaigns in Pega platform for telecommunications company. The main aim of the master thesis is to describe process of marketing campaigns automation, introduce the Pega platform technology and create a methodological framework based on practical experience and real outputs, make a critical evaluation of benefits within proposed methodological practice approach by gathering a feedback from stakeholders of telecommunications company. Presented paper prepares the recommendations and follow up actions for team members of marketing automation project to increase the effectiveness and shorten the time to market of the solutions. Within the master thesis, references from similar projects in south-eastern Europe are also used, as official blueprints from Pega Company are reworked to combine the different sources with various views and achieve the synergy of diverse projects and fields. The results of the master thesis are presented to the business owner of the project and are used as a methodological framework during the project that gives an evidence of contribution of the present paper in practice.